Dataset gratitude cybervictimisation anxiety prospective - Chamizo-Nieto, María Teresa; Rey-Peña, Lourdes (Universidad de Málaga, 2023)
The possible protective factor of gratitude on experiences of cyberbullying behaviours and anxiety symptomatology was examined. A sample of 981 adolescents (55.45% females) participated in a two-wave study, completing three self-report measures. There was a period of 16 weeks between the two data collections. The measuring instruments assessed gratitude (Gratitude Questionnaire: GQ-5), cybervictimisation (European Cyberbullying Intervention Project Questionnaire: ECIPQ) and anxiety symptomatology (Depression, Anxiety and Stress Scales: DASS). A serial mediation analysis was performed to examine the possible predictor role of gratitude on cybervictimisation and anxiety symptomatology. Outcomes reported that gratitude was related to cybervictimisation (Time 1) and anxiety symptomatology (Time 2). Furthermore, a sequential pathway was found from gratitude to cybervictimisation 16 weeks later, firstly through cybervictimisation (Time 1) and then through anxiety symptomatology (Time 2). These findings confirm previous research about the protective role of gratitude to minimise the negative impact of cyberbullying behaviours. Moreover, the first evidence on the potential protective role of gratitude for decreasing the likelihood of suffering cybervictimisation is provided.
Keywords: Adolescentes - Psicología; Gratitud; Cibervictimización; Ansiedad